(untitled) (Global Journal of Human-Social Science, 2021)
Globalization in the current epoch has often had among its trends, to use western cultural paradigms and western cultural values to critique non-western indigenous cultures and their values. This attitude, unfortunately has sometimes given the false impression, not only of racial superiority of Western peoples over non-western peoples but also of the cultural superiority of western cultures and their values over indigenous cultures and cultural values of nonwestern provenance. This has been the issue with the Western culture of postmodernism when viewed from its encounter with indigenous African cultures. Postmodernism comes across as an imperialistic culture, with the intent to effect radical shifts in the very fabric of indigenous cultures and to transform these cultures and their values from the roots. This article examines the tenets of this postmodern culture which often evades the possibility of being captured in a definition. We argue that postmodernism can cause radical but destructive shifts in traditional African cultures and the indigenous values that these cultures define and uphold.